Spectroscopic Analysis of CdO: Fe Plasma Generated by Nd: YAG Laser - Hussein, Tamara S.; Ahmed , Ala F.; Aadim, Kadhim A. (Iraqi Journal of Science, 2022)
In this work, the optical emission spectrum technique was used to analyze the optical emission spectrum of (CdO: Fe) plasma produced by laser Nd: YAG with a wavelength of (532) nm, a period of 10 ns, and a focal length of 10 cm in the energy range of (200-500) mJ. The electron temperature (Te) was determined using the method of line intensities ratio. Using the Saha-Boltzmann equation, the electron density (ne) was determined. Other plasma parameters such as plasma frequency (fp), Debye length (λD) and Debye number (ND) were also measured. The CdO: Fe (at a mixing ratio of X= 0.5.) plasma spectrum was observed for different energies. As a function of the laser energies, the changes in electron temperature and densities were studied. The value of the electron temperature, at X=0.5, was (0.420 - 1.160) eV for laser energy (200-500) mJ, respectively.